Determinant factors influencing the nutrition status of adolescents with intellectual disabilities: a scoping review - Suwito, Maria Rebecca; Widyastuti, Nurmasari; Rahadiyanti, Ayu; Anjani, Gemala; Nurhidayati, Lisa Rosyida (Universitas Gadjah Mada, 2025)
Purpose: This scoping review aims to explore the determinants influencing the nutritional status of adolescents with intellectual disabilities, including macronutrient intake, family income, and other contributing factors. Methods: A systematic search was conducted for articles published from 2012 to 2022 in PubMed, ScienceDirect, and Scopus databases, using keywords such as